Longitudinal Study on Deterrent Effect of Drug-Induced Homicide Law on Opioid-Related Mortality Across 92 Counties and the District of Columbia in the U.S - Lee, Youngeun (Journal of drug issues, 2022)
In response to the opioid epidemic in the United States, the federal and state governments have initiated various public health responses to mitigate the problem. Among others, Drug-Induced Homicide Laws (DIHL) have been introduced to disrupt opioid supply by imposing unconventionally punitive sanctions against sales and distribution. The purpose of this study was to examine whether DIHL had an impact on opioid-related deaths, while controlling for other laws and socioeconomic indices. A dynamic panel model was used with cases from 92 counties across 10 states and the District of Columbia between 2013 and 2018. The findings suggest that DIHL implementation has curtailed the rate of opioid mortality. Supply-interruption approaches may have merits and should be further evaluated.